Forfar and Arneil's textbook of pediatrics - McIntosh, Neil (Edinburgh ; New York : Churchill Livingstone/Elsevier, 2008)
Covers children's health needs and problems in the developing as well as the developed world, with an emphasis on prevention as well as treatment. This book is suitable for pediatricians and family doctors
1. Foundations for health and practice -- 2. Perinatal/neonatal medicine -- 3. The Specialties -- 4. Appendices and index
Includes bibliographical references and index
Keywords: Pediatrics; Pediatrics